Analysis of the role of human papillomaviruses and the p53/Rb tumour suppressor genes in the development of cutaneous squamous cell carcinoma - O'Connor, Darren Patrick (Trinity College (Dublin, Ireland). Department of Microbiology, 2000)
Nonmelanoma skin cancers (NMSC) are the most frequent cancers in Caucasian populations. Renal transplant recipients (RTR) are at an increased risk of neoplasia, particularly skin cancer. Studies on anogenital cancer have highlighted a role for oncogenic human papillomaviruses (HPV) in tumourigenesis, however while HPV infection is necessary for the development of anogenital cancers, it is not sufficient and other factors must also be involved.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin